Path selection algorithm with minimal delay in wireless sensor networks - Tianbo Lu; Yifei Su; Youwen Wang; Xiaoyan Zhang; Hao Meng (International Journal of Distributed Sensor Networks)
With the rapid popularization and development of Internet, global researchers are increasingly paying more and more attention to anonymity and privacy security. Anonymous communication technology has gradually become people’s focus. Attacks against sensors may appear in different layers, so anonymity at network layer should therefore be envisioned. Tor, as one of the anonymous communication systems which implements multi-hop to protect user’s identity privacy on the Internet, is currently the most popular anonymous privacy solution, but the concept of Tor has not applied to wireless sensor networks. Therefore, in this article, we think the mix structure of Tor which is crucial to its anonymity can be applied to wireless sensor networks; what’s more, an improved path selecting algorithm according to round trip time we propose can boost some degree of performance. First, we make a summary of current typical path selection algorithms and analyze the performance and anonymity problems of these algorithms in network congestion. Then, in order to improve the performance of the algorithm in congestion, a routing improvement scheme based on round trip time is proposed.